Optimalisasi Media Digital dalam Desain Pembelajaran Abad 21 - Randi Maulana; Cinta Bayduri Filzah; Gusmaneli Gusmaneli (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
The optimization of digital media in 21st-century learning offers an innovative approach that is more flexible, personalized, and inclusive. This study explores the role of digital media in improving the quality of learning through five key aspects: flexibility and personalization, enhanced collaboration, data-driven learning, real-time evaluation, and inclusivity. Digital media enables students to learn at their own pace and style, expands interactions through virtual platforms, provides immediate feedback, and ensures equal access for students with special needs or from remote areas. The findings reveal that digital media can create a dynamic and responsive learning ecosystem, though its implementation requires adequate infrastructure and supportive educational policies. With effective optimization, digital technology can realize learning that is globally relevant, inclusive, and future-oriented.